The Representation of Learning Zone in the School of Good and Evil Movie - Lisna Riningsih; Adria Vitalya Gemilang; Afria Dian Prastanti (Universitas Sarjanawiyata Tamansiswa, 2025)
This research focuses on the learning zone in the movie The School of Good and Evil. Paul Feig is the director who directed The School for Good and Evil, which is based on Soman Chainani's novel of the same name. The main objective of the research is to determine the impact of people on Agatha's ability to learn in learning zones. Second, determine how Agatha's character develops as she moves through the comfort, learning, and panic zones. To gather and analyze data from the film, the researcher uses Creswell's qualitative methodologies, which are supported by Bogdan. This research focuses on the Zone of Proximal Development (ZPD) proposed by Vygotsky (1979), which Senninger further developed into a learning zone model. The research has limitations in that it only examines one of the main characters, Agatha, as a student at the School for Good. The researcher discovered that the people around Agatha influenced her as she moved through each zone she encountered. Agatha's personality and traits shift while she is in the comfort, learning, and stress zones. To recap, the individuals Agatha meets with, as well as the environment or situations around her, have a big impact on how her character alters in each zone she faces. Keywords: learning zones, character, relationship, interaction